A Heavy Precipitation Event in the Yangtze River Basin Led by an Eastward Moving Tibetan Plateau Cloud System in the Summer of 2016. Issue 15 (6th August 2020) - Chen, Yilun; Zhang, Aoqi; Zhang, Yuheng; Cui, Chunguang; Wan, Rong; Wang, Bin; Fu, Yunfei
Abstract: From 29 June to 6 July 2016, China's Yangtze River Basin experienced heavy precipitation, causing more than 200 deaths and affecting tens of millions of people. Using ERA5 reanalysis, soundings, and satellite observations from FY‐2 and Global Precipitation Measurement (GPM), we reviewed this heavy rainfall event from the perspective of its meteorological triggers and the cloud microphysics. As the cloud system moved eastward from the Tibetan Plateau, precipitation particles got larger and denser, and the enhancement of stratiform precipitation contributed the most precipitation. The riming and aggregation processes, the dominant growth modes of particles, were significantly enhanced between 5.5 and 7 km. The increase in the echo‐top height had a considerable positive effect on the near‐surface particle size (from ~1.0 mm at 4 km to ~1.5 mm at 10 km), but this feature was not significant over the Tibetan Plateau. We suggest that the microphysics of this event was dominated by the combination of the eastward moving cloud system, which acted as continuous "seeder" cloud, and the increase in water vapor associated with the low‐level vortex and jet, which generated enhancing "feeder" cloud. The particles from the "seeder" cloud grew by the lower "feeder" cloud, thus increasing the particle size to enhance the precipitation. Overall, the generation and movement of such a cloud system is an important atmospheric disturbance for the generation of heavy precipitation downstream, and could be an early warning signal in the forecasting of heavy rainfall in China during the Meiyu period. Key Points: An event that produced a historical amount of rainfall in Wuhan during the Meiyu period is reviewed Riming and aggregation processes were enhanced as the cloud system moved out of the Tibetan Plateau The event was dominated by an eastward moving system acting as "seeder" cloud, together with the increasing water vapor acting as "feeder" cloud